Pulse Oximetry as a Diagnostic Tool to Determine Pulp Vitality: A Systematic Review - Alicia Almudever-Garcia; Leopoldo Forner; José Luis Sanz; Carmen Llena; Francisco Javier Rodríguez-Lozano; Julia Guerrero-Gironés; María Melo (Applied Sciences, 2021)
Pulse oximetry (PO) can be used as a technique to assess vascularization. Although it is commonly used in the field of medicine, it still has limited use in dentistry. The aim of this study is to evaluate, by means of a systematic review, if pulse oximetry is a viable and effective system to determine pulp vitality and assess the clinical criteria for its use. A literature search was performed in Medline, Scopus, Embase, and Web of Science databases. Clinical studies using pulse oximetry as a tool to determine pulp vitality in permanent teeth were eligible. Quality assessment of the included studies was performed following the Quality Assessment for Diagnostic Accuracy Studies (QUADAS-2) guidelines. A total of 24 articles were included in the review. The subjective test most compared to PO was the cold test. PO has shown a good sensibility and specificity, and it has been used in different clinical situations. Pulse oximetry has a high potential as a tool for the diagnosis of pulp vitality. However, the absence of a specific pulse oximeter for a dental practice, among other limitations, added to the lack of evidence on how different systemic and oral pathologies may affect the pulp’s oxygen saturation levels, which hinders its clinical use.